Religious Moderation in a Pluralistic World: A Global Bibliometric and Systematic Review (1988–2022) Across Faiths and Regions - Rahayu Subakat; Suwarno Suwarno; Zaini Fasya; Muhammad Hatta (JURNAL AT-TURAS, 2025)
This study investigates the development of scholarly discourse on religious moderation through a bibliometric analysis of international publications indexed in the Scopus database from 1988 to 2022. Employing VOSviewer for visualization and trend mapping, the research analyzes 390 publications, focusing on authorship, publication types, source journals, and keyword trends. The most significant surge in publications occurred in 2019, with articles (77.3%) representing the dominant document type. Notable contributors include Somer Murad and Zarzycka, with leading outputs from journals such as Religions and the Journal of Religion and Health. The United States, the United Kingdom, and Indonesia emerged as key publishing countries. Frequently occurring keywords—religion, moderation, and religiosity—highlight the thematic focus of the literature. Beyond quantitative metrics, the study critically reflects on the conceptual landscape of religious moderation, revealing a growing interdisciplinary engagement yet a lack of consensus on definitional boundaries. These findings offer valuable insights into the evolving scholarly understanding of religious moderation and its implications for pluralistic societies, policy discourse, and interfaith engagement. By linking bibliometric trends to broader theoretical and sociopolitical contexts, this research contributes to a more nuanced comprehension of the field’s intellectual structure and future directions.